Association Between Monocyte to High-Density Lipoprotein Cholesterol Ratio and Risk of Non-alcoholic Fatty Liver Disease: A Cross-Sectional Study - Wang, Liping; Dong, Jinzhong; Xu, Miao; Li, Li; Yang, Naibin; Qian, Guoqing (Frontiers in Medicine, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is a global health problem affecting more than a quarter of the entire adult population. Both monocytes and high-density lipoprotein cholesterol (HDL-C) were found to participate in the progression of hepatic inflammation and oxidative stress. We speculated that the monocyte-to-HDL-C ratio (MHR) may be associated with the risk of NAFLD. Methods We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018. NAFLD was identified using a controlled attenuation parameter (CAP) of ≥274 dB/m. Degree of liver fibrosis were assessed by liver stiffness measurement (LSM) and LSM values≥8.0, ≥ 9.7, and ≥13.7 kPa were defined as significant fibrosis (≥F2), advanced fibrosis (≥F3) and cirrhosis (F4), respectively. The association between MHR and the risk of NAFLD and liver fibrosis was estimated using weighted multivariable logistic regression. The non-linear relationship between MHR and the risk of NAFLD was further described using smooth curve fittings and threshold effect analysis. Results Of 4,319 participants, a total of 1,703 (39.4%) participants were diagnosed with NAFLD. After complete adjustment for potential confounders, MHR was positively associated with the risk of NAFLD (OR = 2.87, 95% CI: 1.95–4.22). The risk of NAFLD increased progressively as the MHR quarter increased (P for trend < 0.001). In subgroup analysis stratified by sex, a positive association existed in both sexes; Women displayed higher risk (men: OR = 2.12, 95% CI: 1.33–3.39; women: OR = 2.64, 95%CI: 1.40–4.97). MHR was positively associated with the risk of significant liver fibrosis (OR = 1.60, 95% CI: 1.08–2.37) and cirrhosis (OR = 1.83, 95% CI: 1.08–3.13), but not with advanced liver fibrosis (OR = 1.53, 95% CI: 0.98–2.39) after full adjustment for potential confounders. In the subgroup analysis by sex, the association between MHR and different degrees of liver fibrosis was significantly positive in women. When analyzing the relationship between MHR and NAFLD risk, a reverse U-shaped curve with an inflection point of 0.36 for MHR was found in women. Conclusion Higher MHR was associated with increased odds of NAFLD among Americans of both sexes. However, an association between MHR and liver fibrosis was found mainly among women.